A new marine ciliate, Apofrontonia jejuensis n. sp. (Protozoa, Ciliophora, Oligohymenophorea) from Jeju Island, South Korea, and an improved diagnosis of the genus Apofrontonia - Quintela-Alonso, Pablo; Omar, Atef; Moon, Ji Hye; Jung, Jae-Ho (Frontiers in Marine Science, 2023)
The genus Apofrontonia comprises vicarious species that until now have only been described in a few locations worldwide. It was assigned to the family Frontoniidae based on two diagnostic features, i.e., the closely arranged kinetal rows in the peniculi and vestibular kineties on the right side of the vestibular cavity’s opening. The first phylogenetic analysis of the genus was based on the 18S rRNA gene, and it was limited not only by the unavailability of other gene sequences from other species within the genus but also by the Peniculia in general. Apofrontonia jejuensis n. sp. was discovered in the coastal waters of Jeju Island, South Korea. Besides the genus-specific features, A. jejuensis n. sp. exhibits a fibrillar system associated with the oral ciliature, likely linked to nematodesmata-like structures, as seen in Frontonia species. This study increases the taxon sampling, offers further insights in the morphological variability of the genus Apofrontonia, and provides additional molecular support for its distinction from the genus Frontonia.